Brain activation induced by psychological stress in patients with schizophrenia - Castro, Mariana Nair (2015)
Environmental influences are critical for the expression of genes putatively related to the behavioral and cognitive phenotypes of schizophrenia. Among such factors, psychosocial stress has been proposed to play a major role in the expression of symptoms. However, it is unsettled how stress interacts with pathophysiological pathways to produce the disease. We studied 21 patients with schizophrenia and 21 healthy controls aged 18 to 50 years with 3T-fMRI, in which a period of 6 min of resting state acquisition was followed by a block design, with three blocks of 1-min control-task, 1-min stress-task and 1-min rest after-task. Self-report of stress and PANSS were measured. Limbic structures were activated in schizophrenia patients by simple tasks and remained active during, and shortly after stress. In controls, stress-related brain activation was more time-focused, and restricted to the stressful task itself. Negative symptom severity was inversely related to activation of anterior cingulum and orbitofrontal cortex. Results might represent the neurobiological aspect of hyper-reactivity to normal stressful situations previously described in schizophrenia, thus providing evidence on the involvement of limbic areas in the response to stress in schizophrenia. Patients present a pattern of persistent limbic activation probably contributing to hypervigilance and subsequent psychotic thought distortions.